مخطوطة "الشافي في الفقه" لأبي العباس أحمد بن محمد الجرجاني الشافعي (ت: 482ه): دراسة وتحقيق لكتاب الطهارة - شبرمي، جوهرة بنت صالح (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Al-Imam Abu al-'Abbas Ahmed b. Muhammad al-Jurjani al-Shafi'i (died 482H) is the subject focus of this dissertation. The researcher choses this prominent figure of Islamic jurisprudence because the obscurity surrounding him and his absence from research and juristic studies even though he belongs a relcnown community of Shafi'i jurists in the 5th century of the itlaltics. The dissertation comprises of two parts. The mojar part consists of a critical edition of the chapter on ritual purity (taharah) in al-Jurjani's wrote under the title “al-Shafi fi al-Fiqh” which is still in manuscript form. To undertake this task, the researcher has followed the established method of editing classical texts including the application of strict rules of maintaining the originality of the edited manuscript, documenting its citations and references, and uncovering its sources as much as possible. The second part of the dissertation is a historical analytical study. It provides a description of al-Jurjani's age and its cultural, intellectual and political circumstances. Then the study introduced al-Jurjani: his personality, factors that contribute to his growth as well as his teachers and students. Finally, this part describes the methodological features of his juristic work. The most important result of this dissertation is that it introduces, for the first time, an eminent jurist who has been ignored by specialists in Islamic jurisprudence, whether those dealing with its history and stages of its development and evolution, those concerned with analyzing its themes and issues, or those interested in introducing its sources and figures.